Stability Analysis in Thin Liquid Film (Immobile Soap Film) - Rotina Al-Etewi; Zena Al-Nuamy (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research is dedicated for analyzing the stability of a system of flow equations for soap film that has opposed for disturbance, and this analysis was done by using Galerkin method which enable to find disturbance growth from its nonexistence after making the system linearization. It was shown through the results of analysis that these equations were in stable state when the real part of wave velocity (a)  is a negative quantity, and it is  unstable state when the real part of this velocity is a positive quantity, i.e. a < 0 we get stability and this happens when the distance (do) and the source (uo) in two similar signs and when a > 0 we get unstable state and this happens when do , uo  have two different  signs.